An artificial intelligence system to predict the optimal timing for mechanical ventilation weaning for intensive care unit patients: A two-stage prediction approach - Liu, Chung-Feng; Hung, Chao-Ming; Ko, Shian-Chin; Cheng, Kuo-Chen; Chao, Chien-Ming; Sung, Mei-I; Hsing, Shu-Chen; Wang, Jhi-Joung; Chen, Chia-Jung; Lai, Chih-Cheng; Chen, Chin-Ming; Chiu, Chong-Chi (Frontiers in Medicine, 2022)
Background: Accurate assessment of the ideal timing for successful weaning from mechanical ventilation (MV) in the intensive care unit (ICU) is very challenging. Purpose: Using artificial intelligence (AI) approach to build two-stage predictive models, namely, the try-weaning stage and weaning MV stage to determine the optimal timing of weaning from MV for ICU intubated patients, and implement into practice for assisting clinical decision making. Methods: AI and machine learning (ML) technologies were used to establish the predictive models in the stages. Each stage comprised 11 prediction time points with 11 prediction models. Twenty-five features were used for the first-stage models while 20 features were used for the second-stage models. The optimal models for each time point were selected for further practical implementation in a digital dashboard style. Seven machine learning algorithms including Logistic Regression (LR), Random Forest (RF), Support Vector Machines (SVM), K Nearest Neighbor (KNN), lightGBM, XGBoost, and Multilayer Perception (MLP) were used. Electronic medical records of intubated ICU patients of Chi Mei Medical Center (CMMC) from 2016 to 2019 were included for modeling. Models with the highest area under the receiver operating characteristic curve (AUC) were regarded as optimal models and used to develop the prediction system accordingly. Results: A total of 5,873 cases were included in machine learning modeling for Stage 1 with the AUCs of optimal models ranging from 0.843 to 0.953. Further, 4,172 cases were included for Stage 2 with the AUCs of optimal models ranging from 0.889 to 0.944. A prediction system (dashboard) with optimal models of two stages was developed and deployed in the ICU setting. Respiratory care members expressed high recognition of AI dashboard assisting ventilator weaning decisions. Also, the impact analysis of with- and without-AI assistance revealed that our AI models could shorten the patients’ intubation time by 21 hours. Conclusion: Two-stage AI prediction models could effectively and precisely predict the optimal timing to wean intubated patients in the ICU. This could reduce patient discomfort, improve medical quality, and lower medical costs. AI-assisted prediction system is beneficial for clinicians to cope with a high demand for ventilators during the COVID-19 pandemic.